Attitudes of special education teachers of pupils with intellectual diability towards the inclusion of computers in their curriculum - Tan, Anthony Kok Poh. (2008)
The study was conducted to investigate the attitudes of special education teachers of pupils with intellectual disability towards the inclusion of computers in teaching and learning. The study also investigated the factors affecting the teachers’ attitudes and their concerns pertaining to the inclusion of computers.